(untitled) (American Journal of Islam and Society, 1997)
Since its inception fourteen years ago, AJZSS has built a considerable reputation as an academic Islamic journal. In addition to being a global forum for intellectual exchange between Muslim academicians from various disciplines, AJZSS has contributed to efforts at Islamization of knowledge and the reorientation of Islamic thought. And while the Journal has made sigmficant strides in reorienting Islamic thought, AJZSS cannot be the sole provider of guidance for the Islamization of knowledge effort. Certainly, the necessary radical reorientation of knowledge will only occur with planned coordination with other academic activities, conferences, seminars, study circles, etc., and with the contributions of other individuals and communities of scholars from various parts of the world and academic disciplines. From time to time, the Journal must stress the importance of Islamic epistemology as the framework for its academic efforts. In view of our ever-developing understanding of theoretical principles drawn from authentic sources, and also in view of developing issues and challenges, it is important to re-examine this framework to confii that it is indeed appropriate. If the Islamic epistemology is functioning appropriately, it should define an Islamic methodology for resemh and inquiry in all topics and issues =levant to the Journal. All research articles should state its methodology, which should be consistent with our system of knowledge, as well as interpret results within its own framework by using the needed instruments and procedures for collecting and analyzing relevant data and evidence. Although the Journal has dealt with these two themes, namely, epistemology and methodology, they still need to be defined definitively. Muslim scholars and researchers should not just refer to Islamic epistemology and Islamic methodology as a given or something known and understood; mther, they need to delve deep into the very heart of these matters to provide more in-depth and thought-provoking contributions. We understand that many of our Muslim scholars find themselves under the pressure of their practical circumstances when choosing their research topics. In the upcoming issues, God willing, the Journal will facilitate the endeavors of the authors to make their contributions more ...